58.7k views
0 votes
Need An Answer ASAP ... THANK YOU !!!

Need An Answer ASAP ... THANK YOU !!!-example-1
User Ingenious
by
5.2k points

1 Answer

6 votes

Answer:

∠EFG = 48°

Explanation:

As FH bisects ∠EFG , ∠EFH = ∠HFG .

We know that ∠EFH = (-5x + 89)° . So ∠HFG = ∠EFH = (-5x + 89)°

Also, ∠HFG + ∠EFH = ∠EFG

=> 2(-5x + 89)° = (61 - x)°

=> -10x + 178 = 61 - x

=> 10x - x = 178 - 61

=> 9x = 117

=> x = 117 / 9 = 13

Putting the value of 'x' in ∠EFG gives :-

(61 - x)° = (61 - 13)° = 48°

User Joris Schellekens
by
5.9k points